Visualization of Basic Mathematics Teaching Based on Artificial Intelligence - Wu, Ronghua (Journal of physics. Conference series, 2021)
Basic mathematics is an important part of education and teaching in our country. As a basic subject in our country’s teaching, it has always played an important role. However, with the development of time, the traditional mathematics teaching methods can not stimulate students’ interest in mathematics. In order to find out the teaching mode to improve students’ level and enthusiasm, based on artificial intelligence, this paper uses case analysis method, literature analysis method and other methods to collect data from the database, builds a model based on artificial intelligence, and reads and analyzes a large number of relevant literature through literature survey method, according to the research needs, through the research and summary of literature content. Research structure found that through the teaching of artificial intelligence, students’ mathematics scores are about 30% higher than the traditional teaching methods, the sense of cooperation between students reaches 0.8, to solve the contradiction between popularization and improvement, and to solve the polarization and the transformation of backward students and other problems, so that their personality can be fully developed and developed, so that mathematics teaching in Colleges and universities to the track of quality education. This shows that the basic mathematics teaching based on artificial intelligence can play an important role in college education.